Management of ST Elevation Myocardial Infarction (STEMI) in Different Settings - Partow-Navid, Rod; Prasitlumkum, Narut; Mukherjee, Ashish; Varadarajan, Padmini; Pai, Ramdas G. (International Journal of Angiology, 2021)
ST-segment elevation myocardial infarction (STEMI) is a life-threatening condition that requires emergent, complex, well-coordinated treatment. Although the primary goal of treatment is simple to describe—reperfusion as quickly as possible—the management process is complicated and is affected by multiple factors including location, patient, and practitioner characteristics. Hence, this narrative review will discuss the recommended management and treatment strategies of STEMI in the circumstances.
Keywords: acute coronary syndrome; PCI; thrombolysis; STEMI; management; review article; different settings